URBAN POVERTY: EVIDENCE FROM LAMPUNG PROVINCE - Ahmad Rifa'i (Economic Journal of Emerging Markets, 2011)
One of the big issues in economic development is poverty. This paper models the poverty in Bandar Lampung and Metro cities in Lampung Province for the period of 2002 to 2007. It estimates a linear regression model using secondary data. The results show that per capita income and dependence ratio significantly influence the poverty, and that education level does not significantly influence the poverty. It also uncovers the existence of structural poverty in the area, indicated by the evidence of income in-equality.